The Role of Omega-3 Fatty Acids in the Pathophysiology and Treatment of Migraine: An Updated Review of Clinical Evidence, Mechanistic Pathways and Nutritional Recommendations - Wojciechowska, Karolina; Izabela Zajkowska,; Zabrocka, Patrycja; Martowska, Julia; Choroszewska, Ewelina; Baran, Julia; Warych, Wiktor (Quality in Sport, 2026)
Migraine is a complex neurological disorder in which neuroinflammatory processes, altered neuronal excitability, mitochondrial dysfunction, and changes within the immunological microenvironment play key roles in its pathophysiology. Omega-3 fatty acids, particularly EPA and DHA, exhibit potent anti-inflammatory, pro-resolving, and neuroprotective effects. This article provides a narrative review of the literature describing the mechanisms of action of omega-3 fatty acids and their clinical efficacy in studies related to migraine. Background: Migraine is one of the most diagnosed neurological disorders and significantly impacts patients’ quality of life. Current understanding highlights its neuro-immunological nature, involving complex interactions between neurons, glial cells, and inflammatory mediators. In recent years, increasing attention has been directed toward nutritional factors that may modulate the course of the disorder, including omega-3 fatty acids. Aim: The aim of this article is to provide an expanded narrative review of the mechanisms of action of omega-3 fatty acids and to evaluate their clinical effectiveness in the context of migraine prevention and treatment. Material and Methods: This review has a narrative character. The literature was searched in the PubMed, Scopus, and Web of Science databases for the years 2000- 2025, using keywords related to migraine and omega-3 fatty acids (including migraine, omega-3 fatty acids, EPA, DHA, resolvins, CGRP). Experimental studies, clinical trials, and reviews addressing the role of EPA and DHA in the pathophysiology and treatment of migraine were included. Publications of low methodological quality or lacking complete data were excluded. The aim of this review was to provide a synthetic summary of current knowledge rather than to conduct a systematic review. Results: The reviewed evidence indicates that omega-3 fatty acids, particularly EPA and DHA, influence several biological pathways relevant to migraine pathophysiology. Mechanistic studies consistently demonstrate their ability to modulate pro-inflammatory lipid mediators, enhance the production of pro-resolving molecules, stabilize neuronal membranes, improve mitochondrial efficiency, and reduce CGRP-related neurovascular activation. Clinical trials show heterogeneous but generally favourable outcomes, with the most pronounced benefits observed in interventions that include increased EPA intake combined with dietary reduction of omega-6 fatty acids and treatment durations of at least 12 weeks. Adjunctive therapies involving omega-3 fatty acids, such as combinations with valproate or metabolic cofactors, also suggest potential synergistic effects. Evidence in paediatric populations remains limited and inconsistent. Conclusions: Omega-3 fatty acids represent a promising adjunctive strategy in migraine management, supported by mechanistic plausibility and growing clinical evidence. Their therapeutic potential appears strongly context-dependent, particularly on dietary omega-6 intake and treatment duration. EPA-rich formulations may offer enhanced anti-inflammatory and migraine-preventive effects, while DHA contributes to neuroprotection and neuronal stability. Although current findings are encouraging, larger and methodologically rigorous clinical trials are needed to establish optimal dosing, treatment protocols, and biomarkers that could guide personalized omega-3-based interventions in migraine care.